2009
DOI: 10.1007/s00198-009-1036-5
|View full text |Cite
|
Sign up to set email alerts
|

Selecting men for bone densitometry: performance of osteoporosis risk assessment tools in Portuguese men

Abstract: Summary Clinicians need tools to identify patients most likely to benefit from bone mineral density (BMD) testing, for which cost-effectiveness does not allow generalized screening. This study supports the utility of osteoporosis risk assessment tools in selecting men for BMD testing. Different cutoff values may be appropriate for different countries and/or ethnic origins. Introduction Our aim was to evaluate the utility of three osteoporosis (OP) risk assessment tools in a large group of Portuguese men aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Although osteoporosis is less prevalent in men than women, 30% of hip fractures occur in men [26] and comprise around 25% of the total cost burden [2]. Similar supporting correlations have also been reported from OSTA studies in men [17,18,25,27]. In addition, studies on OSTA report strong correlations not only for the Taiwanese population [28,29] but also for populations of the Philippines, Japan, Korea, Malaysia, Thailand, Singapore, and China [16,19,20,21,22,23,24,30].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although osteoporosis is less prevalent in men than women, 30% of hip fractures occur in men [26] and comprise around 25% of the total cost burden [2]. Similar supporting correlations have also been reported from OSTA studies in men [17,18,25,27]. In addition, studies on OSTA report strong correlations not only for the Taiwanese population [28,29] but also for populations of the Philippines, Japan, Korea, Malaysia, Thailand, Singapore, and China [16,19,20,21,22,23,24,30].…”
Section: Introductionsupporting
confidence: 65%
“…The risk of osteoporosis in the high-, medium- and low-risk categories was found to be 61%, 15% and 3%, respectively [16]. A significant positive correlation was found between the OSTA index and T-scores of BMD measured by dual energy X-ray absorptiometry at the femoral neck [24,25]. The probability of a patient with an OSTA score < −4 having osteoporosis is 53.8% [23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that evaluated OST for women reported performance estimates ranging from a high sensitivity of 99 % and corresponding specificity of 15 % with use of a threshold of <6 to identify perimenopausal and early postmenopausal women in Denmark with osteoporosis [96] to a low sensitivity of 17.7 % (95%CI 16.0–19.5 %) and corresponding specificity of 95.7 % (95%CI 94.8–96.4 %) with use of a threshold of −3 to identify postmenopausal women in Argentina with osteoporosis [100]; AUCs ranged from 0.652 (95%CI 0.604–0.699) [72] to 0.77 [95]. Studies that evaluated OST to identify men with osteoporosis or low BMD at the femoral neck, total hip, or lumbar spine reported performance estimates ranging from a high sensitivity of 93 % and corresponding specificity of 66 % with use of a threshold of 3 to identify US male veterans with osteoporosis [11] to a low sensitivity of 6 % and corresponding specificity of 94 % with use of a threshold of −2 to identify US men with rheumatoid arthritis with osteoporosis [92]; AUCs ranged from 0.590 (95%CI 0.492–0.688) when evaluating OST with a threshold of <4 in Portuguese men aged ≥50 [73] to 0.993 in a subgroup analysis of US male veterans aged ≥80 [11]. …”
Section: Resultsmentioning
confidence: 99%
“…Reported sensitivities and specificities for OSTA for identifying men with osteoporosis at the femoral neck, total hip, or lumbar spine ranged from a high sensitivity of 87.33 % and corresponding specificity of 56.20 % with use of a threshold of ≤−1 for Chinese men aged ≥50 years [69] to a low sensitivity of 38.2 % and corresponding specificity of 82.1 % with use of a threshold of <1 for Portuguese men aged ≥50 years [73]; AUCs ranged from 0.597 (95%CI 0.497–0.697) [73] to 0.676 (95%CI 0.612–0.732) [117]. …”
Section: Resultsmentioning
confidence: 99%
“…The risk of osteoporosis in the high-, medium- and low- risk patients was found to be 61%, 15% and 3%, respectively [3,6]. The OSTA score has a significant positive correlation with the T-scores of bone mineral density as measured by dual-energy X-ray absorptiometry [7,8], and has been validated as an effective and feasible screening method in many Asian countries [3,6,7,9,10,11,12,13,14] to identify both men and women [4,8,15,16] with low bone mineral density who are at risk for osteoporosis.…”
Section: Introductionmentioning
confidence: 99%